Overall Reliability Optimization of a Production System - Billal Nazim Chebouba; Mohamed Arezki Mellal; Smail Adjerid (University of Eloued, 2019)
At the present time, the competitiveness in the industrial world became more and more harsh, which requires that the system must be as reliable as possible. In most of the optimization problems, hard fitness functions are considered. These functions cannot be solved by the traditional mathematical methods. An alternative solution to the conventional approaches is the use of meta-heuristic optimization techniques, due to their ability to obtain global or near-global optimum solutions. In the present paper, we address the overall system reliabilityredundancy allocation optimization problem of a production system (pharmaceutical production line), using a powerful algorithm called the Stochastic Fractal Search (SFS). The constraints of the problem are handled by resorting to the penalty function method
Intervention
Keywords: Reliability; Production system; Optimization; Stochastic fractal search